Hi there!
Assuming "Find the product" means multiplying (4x-3) by (3x+8) and factor to it's simplest form the answer would be:
12x²+23x-24
The way you solve this is by using the distributive property of multiplication as shown below:
Start by multiplying -3 from (4x-3) by everything in (3x+8)
3x*(-3) = -9x
8*(-3) = -24
Once you've done that you then multiply everything 4x
4x*8 = 32x
4x*3x = 12x²
(Note: when multiplying two of the same variables like x it means you are multiplying x by itself which is the same as x²)
When you put all of this together it looks like this
12x²+32x-9x-24
from there we combine like terms
32x-9x = 23x
to get
12x²+23x-24
I hope this helps!
God bless,
ASIAX
Answer:
C. 56°
Step-by-step explanation:
An isosceles triangle has two sides that are equal. ∆ABC has two equal sides. Thus, the angles opposite the two sides of an isosceles triangle are also congruent to each other.
<C and <A are congruent to each other.
m<A = 56°, therefore,
m<C = 56°
Answer:8 times 4+12+= 44
Step-by-step explanation:
8 times 4 gives you 32 then add 12 to get 44
Answer:
Step-by-step explanation:
When a circle is rolled out, the base becomes πr and the heignt of each cone becomes r, therefore when the circle is made the equation become πr²
Answer:
45 teens
Step-by-step explanation:
9+2=11
55/11=5
9x5=45